Enhancing Early Childhood Learning Outcomes Through Innovative Teaching Methods at RA Al-Hurriyah - Dian Triani; Suryani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of innovative teaching methods in enhancing early childhood learning outcomes at RA Al-Hurriyah. Early childhood education is a crucial stage in a child’s development, as it lays the foundation for future learning and growth. However, traditional teaching approaches often fail to fully engage young learners, resulting in limited cognitive and social development. To address this issue, the research focuses on implementing creative and interactive teaching strategies that foster active participation, curiosity, and a love for learning in young children. The study was conducted over two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data was collected through classroom observations, assessments, and interviews with teachers and parents. The findings indicate that the use of innovative teaching methods significantly improved children’s cognitive, emotional, and social development. Strategies such as hands-on activities, play-based learning, and multimedia resources helped make learning more enjoyable and meaningful. Children showed increased engagement, improved problem-solving skills, and better social interactions with peers. Additionally, the research revealed that these teaching methods not only enhanced learning outcomes but also fostered a positive classroom environment. The study concludes that adopting innovative teaching methods in early childhood education, especially in RA Al-Hurriyah, plays a vital role in shaping well-rounded, confident, and motivated learners. These findings provide valuable insights for educators seeking to improve early childhood education through more engaging and effective teaching practices.